POETIC INTERPRETATION OF THE QUR'AN AND SUNDANESE LITERATURE: PUPUJIAN POEM OF WAL FAJRI BY K.H.E.ABDULLAH - Nugraha, Roni (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
This article examines the poetic explanation of K.H.E. Abdullah (1918-1994) about time in Q.S. al-Fajr [89]: 1-5. The poem K.H.E. Abdullah not only interprets Q.S. al-Fajr [89]: 1-5 as a phenomenon of the circulation of time in the universe but also as a metaphor for the journey of human life. His interpretation was published in the Iber Sundanese magazine in the October-December 1970 edition in the rubric of Tafsir Al-Qur'an. E. Abdullah is the second generation activist of the Islamic Unity organization (PERSIS) after A. Hassan. Based on library research and the descriptive-analytical method, this article shows that the verse about the phenomenon of time in al-Fajr/89: 1-5 is interpreted metaphorically as a description of human life in the world. The word al-Fajr means youth before ruruntuk (old age) comes. Laya>l 'asr is interpreted as alternating nights describing the increasing age. Al-syaf' interpreted as a whole moon night, represents a perfect age as an adult. Al-watr interpreted when the night turns dark reflects the time of getting older. The passage of youth into old age means wa al-layl iz> yasr (by night when it passes). From the Sundanese literary approach, E. Abdullah's pupujian poem generally shows the works that refer to the rules of pupujian, as seen in the number of lines, syllables of arrays, and the final rhyme of each line (a-a-a-a). This pupujian poem emphasizes that although E. Abdullah is active in the modernist Islam movement, he still preserves the tradition of pupujian in his work to bring himself closer to the local culture.